Detoxification of aflatoxin M1 in dairy products by saccharomyces cerevisiae - Sara Abdallah Gameh Ahmed; Ahmed Abdelrhman Ismaiel; Mohsen Abouelela Sayed; Nagwa Abdelhamed Tharwat (Cairo : Sara Abdallah Gameh Ahmed, 2020)
The most common and economically important traditional dairy products in Egypt are raw milk, Karish cheese (an Arabian dairy product made from defatted cow milk) and Zabady (Arabian yoghurt made from buffalo and cow milk). In this study, 302 traditional dairy samples including raw milk (120), white Karish cheese (118), and Zabady (64) were analyzed for aflatoxin M1 (AFM1) during different seasons in 2016 and 2017. Contamination of raw milk samples with AFM1 was 21.6% and 18.3% in samples collected in the two respective years with percentages of 100% and 90.9% exceeding the legal European limit (0.05 og L-1). In Karish cheese samples, the contamination level was 33.9% and 44.6%, in the two years examined with percentages of 90.47% and 80% that were above the European limit (0.25 og kg-1). In the case of Zabady, the AFM1-positive samples were 12.5% and 18.75%, and all of them were above the European limit (0.25 og kg-1). However, average toxin concentration in Zabady was lower than that detected in milk and cheese. Despite the seasonal variations influencing the occurrence of AFM1 in the three dairy products, the AFM1 levels in samples collected in winter were significantly (P {u2264} 0.001) greater than those collected in summer.The contamination levels of AFM1 in Egypt, considered a critical issue which affect public health. The traditional dairy products consumed in Egypt; represent a serious health risk. It is urgent to inspect dairy farms for contamination with aflatoxins (AFs) in a regular manner
Thesis (M.Sc.) - Cairo University - Faculty of Science - Department of Botany and Microbiology
Issued also as CD
Keywords: Aflatoxin M1 (AFM1); Incidence; Survey